Models Quality of Electronics Products - Eidukas, D.; Kalnius, R. (Elektronika ir Elektrotechnika, 2010)
This publication is about continuous between-operational control main probabilities characteristics modelling techniques for multilevel EP, when separate independent parameters defect level probabilities distributions are set (known) in chosen control schematics place. Denied EP streams go back to production process for regeneration and classification rules, in different control levels, are similar. Made EP defect level probability density direct and reverse transformations models by separate parameter levels densities transformations. Offered to use approximated models instead of whole EP defect level probabilities density transformed models because of complicated process of integration and models get more simple expressions. Ill. 6, bibl. 18 (in English; abstracts in English, Russian and Lithuanian).